Electric Jesus [videorecording (DVD)] - White, Chris; Baumgartner, Brian; Nelson, Judd; Eakle, Andrew (1091, 2021)
When a flashy promoter sells a Christian metal band on the promise of a summer tour in 1986, their desire to 'make Jesus famous' meets the complexities and confusion of personal ambition, youthful zeal, lifelong friendships, and first love.